Case Report: Minimally invasive management of suspected active bleeding from intercostal vessel after axillary thoracotomy ventricular septal defect repair: an application of Foley catheter - Tian, Yunfei; Huang, Erjia; Zhang, Mengdi; Fan, Jinzhe; Li, Wei; Yang, XiaoHui; Su, Wei; Deng, Xicheng (Frontiers in Cardiovascular Medicine, 2025)
The right axillary thoracotomy, an alternative approach for selected open-heart procedures, offers aesthetic advantages. However, intercostal vessel injury is a potential postoperative complication that can lead to major bleeding. Herein, we report a case of postoperative active bleeding from intercostal vessel injury after right axillary thoracotomy for ventricular septal defect repair. Hemorrhage was successfully halted by compressing the suspected bleeding site with a Foley catheter inserted through the chest wall. This case demonstrates a simple management method of active intercostal vascular bleeding after cardiac operation. It may be an appropriate option in selected postoperative patients with a high index of suspicion of intercostal vascular bleeding after operation via a thoracotomy approach.